Practical recommendations for endurance cycling in hot/humid environments - Nichols, D. (ASPETAR Sports Medicine Journal, 2016)
Cyclists should heat acclimate for at least 1 week, but ideally 2 in a similar environment to that in which they will compete. Sessions should last at least 60 minutes a day and induce a marked increase in body core and skin temperatures, as well as stimulate sweating. • Adequate fluid and salt should be consumed before, during and after training or competition to ensure euhydration (monitored by body mass and urinary markers). • Specific countermeasures should be implemented before (pre-cooling: fanning, ice-cooling vests, cold water and ice slurry ingestion) and during (percooling: `ice socks`) competition to reduce heat storage and physiological and perceptual strain. • Light coloured apparel (helmet, jersey, shorts and shoes) which promotes airflow should be selected over dark coloured, aerodynamic kit (time trials maybe an exception to this).